2005
DOI: 10.1590/s0100-204x2005000300001
|View full text |Cite
|
Sign up to set email alerts
|

Bemisia tabaci, Brevicoryne brassicae and Thrips tabaci abundance on Brassica oleracea var. acephala

Abstract: Bemisia tabaci, Brevicoryne brassicae and Thrips tabaci on Brassica oleracea 197Bemisia tabaci, Brevicoryne brassicae and Thrips tabaci abundance on Brassica oleracea var. acephalaGermano Leão Demolin Leite (1) , Marcelo Picanço (2) , Gulab Newandram Jham (3) and Márcio Dionízio Moreira Abstract -Kale Brassica oleracea var. acephala is attacked by whitefly Bemisia tabaci, aphid Brevicoryne brassicae and Thrips tabaci. One of the main reasons for extensive insecticide application is the lack of informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
2
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 15 publications
2
21
2
2
Order By: Relevance
“…Species of insects such as thrips which have a developmental stage in the soil are strongly influenced by rainfall (Silveira Neto et al, 1976). The results obtained in this study are in agreement with those obtained by Leite et al (2005).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Species of insects such as thrips which have a developmental stage in the soil are strongly influenced by rainfall (Silveira Neto et al, 1976). The results obtained in this study are in agreement with those obtained by Leite et al (2005).…”
Section: Resultssupporting
confidence: 92%
“…An increase in thrips was observed starting in the summer (Figure 1) and continuing throughout the three cycles, contrary to the results obtained by Leite et al (2005) who found no significant differences in the occurrence of T. tabaci in Brassica oleracea var. acephala.…”
Section: Resultscontrasting
confidence: 87%
See 1 more Smart Citation
“…Several factors such as climatic conditions (Gonçalves, 1997), crop fertility status, age and growth rate (Marschner, 1995), natural enemies and leaf chemical composition (Eigenbrode & Pillai, 1998;Leite et al, 2005) can influence insect population in plants.…”
Section: Introductionmentioning
confidence: 99%
“…5). As médias seguidas pela mesma letra na linha não diferem, entre si, pelo teste de média de Scott-Knott ao nível de 1% de significância Os insetos, com destaque para os sugadores, atacam preferencialmente as folhas apicais, principalmente a face inferior no início do cultivo, por estas serem mais tenras, com menores quantidades de cálcio e de fibras, e de alto valor nutricional com alto teor de nitrogênio (CHAU et al, 2005;LEITE et al, 2002LEITE et al, , 2005SANTOS et al, 2003;SILVA et al, 1998). Em contraste, no presente trabalho foi observado maior ataque de cigarrinhas na face superior, provavelmente devido à maior presença de tricomas na face inferior.…”
Section: Methodsunclassified